2020
DOI: 10.1016/j.cmi.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

How to interpret MICs of antifungal compounds according to the revised clinical breakpoints v. 10.0 European committee on antimicrobial susceptibility testing (EUCAST)

Abstract: ¼ 2) and posaconazole (ATU ¼ 0.25) against A. terreus. Implications: EUCAST-AFST has released ten new documents summarizing existing and new breakpoints and MIC ranges for control strains. A failure to adopt the breakpoint changes may lead to misclassifications and suboptimal or inappropriate therapy of patients with fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 36 publications
4
135
0
2
Order By: Relevance
“…The A. nomiae isolate in our patient was resistant to AMB (S ≤ / > R = 1/1) according to the latest drug resistance criteria (Arendrup et al, 2020). This resistance permitted angioinvasion by the fungus, which led to treatment failure.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The A. nomiae isolate in our patient was resistant to AMB (S ≤ / > R = 1/1) according to the latest drug resistance criteria (Arendrup et al, 2020). This resistance permitted angioinvasion by the fungus, which led to treatment failure.…”
Section: Discussionmentioning
confidence: 76%
“…The MIC endpoints for itraconazole, voriconazole, posaconazole, and AMB were determined using a reading mirror as the lowest concentration of the drug that prevented any recognizable growth (100% inhibition). The MIC results were interpreted according to the revised clinical breakpoints v. 10.0 of the European Committee on Antimicrobial Susceptibility Testing (EUCAST), who defines new criteria for resistance to AMB (S ≤ / > R = 1/1) (Arendrup et al, 2020). The other revised breakpoints include itraconazole (ATU = 2) and isavuconazole against A. flavus (S usvuszolevucoATU = 2); isavuconazole (S ≤ / > R = 1/2, ATU = 2), itraconazole [S conazole (S oATU = 2)], posaconazole (ATU = 0.25), and voriconazole [S conazole (S iATU = 2)] against A. fumigatus, itraconazole (S conazoletracoATU = 2), and voriconazole [S conazole (S nATU = 2)] against Aspergillus nidulans, AMB against Aspergillus niger (S rgerst n B) against itraconazole [S conazole (S gATU = 2)], and posaconazole (ATU = 0.25) against Aspergillus terreus.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…The remaining ten voriconazole‐resistant isolates showed MIC values of 2 mg/L, falling within the Area of Technical Uncertainty (AUT), previously named ‘intermediate category’; however they can't be considered wild‐type (WT) according to EUCAST Epidemiological Cut‐OFF values (WT ECOFF ≤ 1 mg/L). 22 …”
Section: Resultsmentioning
confidence: 99%
“…Using the former CB for micafungin of C. albicans, a frequent misclassification for borderline resistant strains was noted. Arendrup et al recently reported ten isolates of C. albicans with a micafungin MIC of 0.032 mg/L and an anidulafungin MIC of up to 0.032 mg/L without any target mutations in the hot spot regions [22], thus underlining that the former CB misclassified the genotypical wildtype strains as resistant. We observed the same phenomenon in an even higher number of C. albicans isolates (n = 86).…”
Section: Discussionmentioning
confidence: 99%